Assessment of communication disorders in children : resources and protocols - Hegde, M. N. (Mahabalagiri N.), 1941-; Pomaville, Frances (Plural Publishing, Inc., 2022)
"Assessment of Communication Disorders in Children: Resources and Protocols, Fourth Edition offers a unique combination of scholarly information, invaluable resources, and time-saving protocols on assessment of the full range of communication disorders in children, including nonverbal or minimally verbal children. Most resource books offer limited research and scholarly information, thus making them unsuitable as textbooks for academic courses on assessment and diagnosis. Similarly, most traditional textbooks do not include practical, easy-to-use, and time-saving resources and protocols that the practicing clinicians can readily use during assessment sessions. By combining the strengths of traditional texts with newer assessment resources and protocols, this one-of-a-kind book offers a single, comprehensive source that is suitable as a textbook and useful as a practical clinical resource"--